Evaluative Study On The Development Potential Of The Purwokerto Station Area Based On Transit Oriented Development - Artanti Kusuma Ayu; Safety Husna Pangestika; Muhammad Azmy Ikhsani (Jurnal Ilmiah Dinamika Rekayasa, 2025)
Purwokerto Station is a major transportation hub in Banyumas Regency with significant potential to bed developed into a Transit Oriented Development (TOD) area. This study aims to evaluate the sustainability of the area within an 800-meter radius from the station based on six core TOD principles : walkability, mixed-use, connectivity, density, transit service, and public space. The method used is a descriptive approach based on literature review, planning documents, as well as spatial and visual data. The assessment was conducted using a scoring system with technical indicators for each aspect on a scale of 0 to 5. The evaluation results show that area only score 14 out of 30 (46,67%), indicating a low level of TOD compliance. While connectivity and transit service performed moderatly, aspects such as walkability, mixed-use, and public space remain far from the ideal standard. These findings highlight the need for re-planning strategies and RDTR policy revisions to support TOD principles, including improving pedestrian infrastructure, integrating transport modes, and providing public spaces. This research serves as an important foundation for the sustainable development of TOD-based areas in Purwokerto.